2014
DOI: 10.1093/mnras/stu094
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency A-type pulsators discovered using SuperWASP★†

Abstract: We present the results of a survey using the WASP archive to search for high frequency pulsations in F-, A-and B-type stars. Over 1.5 million targets have been searched for pulsations with amplitudes greater than 0.5 millimagnitude. We identify over 350 stars which pulsate with periods less than 30 min. Spectroscopic follow-up of selected targets has enabled us to confirm 10 new rapidly oscillating Ap stars, 13 pulsating Am stars and the fastest known δ Scuti star. We also observe stars which show pulsations i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 54 publications
4
99
0
Order By: Relevance
“…HD 24355 is a bright (V = 9.65) rapidly oscillating Ap star, discovered by Holdsworth et al (2014a). Their data show a pulsation at 224.31 d −1 (2596.18 µHz; P = 6.4 min) with an amplitude of 1.51 mmag in the WASP broadband filter.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…HD 24355 is a bright (V = 9.65) rapidly oscillating Ap star, discovered by Holdsworth et al (2014a). Their data show a pulsation at 224.31 d −1 (2596.18 µHz; P = 6.4 min) with an amplitude of 1.51 mmag in the WASP broadband filter.…”
Section: Introductionmentioning
confidence: 96%
“…They show pulsations in the range of 6 − 23 min with amplitudes up to 18 mmag in Johnson B (Holdsworth 2015), and are found at the base of the classical instability strip on the Hertzsprung-Russell (HR) diagram, from the zero-age main-sequence to the terminal-age main-sequence in luminosity. Since their discovery by Kurtz (1982), only 61 of these objects have been identified (see Smalley et al 2015 for a catalogue).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reveal over 350 stars which pulsate with periods less than 30 minutes; among them 10 new roAp, 13 pulsating Am stars and the fastest known pulsating δ Scuti stars. Holdsworth et al (2014b) reported the safe detection in the Kepler and WASP data sets of pulsation frequency variations in the roAp star KIC 7582608. They concluded that one possibility for the frequency variation is intrinsic variability in the pulsation cavity or the binary motion.…”
Section: Main Sequence A-f Starsmentioning
confidence: 99%